TRANSFORMASI PENDIDIKAN TINGGI MELALUI KECERDASAN BUATAN (Ai) DALAM PEMBELAJARAN DAN TATA KELOLA KAMPUS - Saputra, Adi Jaya; Suanti, Dwi Sari; Satria, Median (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The digital transformation of higher education requires the adaptive and responsible use of Artificial Intelligence (AI). This community service activity aimed to enhance the literacy and readiness of the academic community in utilizing AI to support learning processes and campus governance. The methods included interactive lectures, guided discussions, and demonstrations of AI applications in academic contexts. The results indicate improved participants’ understanding of AI concepts, benefits, and limitations, as well as the formulation of AI implementation recommendations aligned with Learning Outcomes (CPL) and the Outcome-Based Education (OBE) approach. Overall, this activity contributes to strengthening institutional readiness toward the development of an adaptive and data-driven smart campus. Keywords : artificial intelligence; higher education; learning; smart campus; community service Abstract: Transformasi digital pendidikan tinggi menuntut pemanfaatan kecerdasan buatan (Artificial Intelligence/AI) secara adaptif dan bertanggung jawab. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan literasi dan kesiapan sivitas akademika dalam memanfaatkan AI untuk mendukung pembelajaran dan tata kelola kampus. Metode kegiatan meliputi ceramah interaktif, diskusi terbimbing, dan demonstrasi pemanfaatan AI dalam konteks akademik. Hasil kegiatan menunjukkan peningkatan pemahaman peserta mengenai konsep, manfaat, dan batasan penggunaan AI serta tersusunnya rekomendasi implementasi AI yang selaras dengan Capaian Pembelajaran Lulusan (CPL) dan Outcome-Based Education (OBE). Kegiatan ini berkontribusi dalam memperkuat kesiapan institusi menuju pengembangan kampus cerdas (smart campus) yang adaptif dan berbasis data. Kata Kunci: kecerdasan buatan; pendidikan tinggi; pembelajaran; smart campus; pengabdian masyarakat